Effectiveness of the Village Government Organization of Cibarusah City, Cibarusah District, Bekasi Regency - Khoirunisa, Efri; Priyanti, Evi; Atthahara, Haura (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2025)
This study aims to determine the effectiveness of the Cibarusah City Village government organisation reviewed using the theory of effectiveness consisting of aspects of adaptability, productivity, and job satisfaction. Using a qualitative research type with a case study approach and descriptive in nature, data collection was carried out using observation, interview, and documentation techniques, then data analysis was carried out in stages starting from reduction and presentation to verification and drawing conclusions. The results of the study indicate that the effectiveness of the Cibarusah City Village government organisation, seen from the aspects of adaptability, productivity, and job satisfaction, is quite good. It's just that there are still aspects of productivity and job satisfaction that are not perfect. Such as in the productivity aspect, it has not been able to reach a qualified level in terms of its service. As well as in the aspect of job satisfaction that has not reached the level of job satisfaction in the employee incentive indicator. This study can be used as a reference to determine the effectiveness of government organisations implemented by agencies, especially village governments. The discipline of science in this study is the discipline of government with a sub-discussion of village government organisations. The novelty of this study is that it reviews the effectiveness of government organisations implemented by the Cibarusah City Village Government, Cibarusah District, and Bekasi Regency.